Behavior of Extended End-Plate Moment Connections Subject to Cyclic Loading - Sumner, Emmett A; Murray, Thomas M (Journal of structural engineering (New York, N.Y.), 2002)
Extended end-plate moment connections are one alternative to fully welded connections that has been considered for use in seismic force resisting moment frames. As a part of the SAC Steel Project, a research program to investigate the behavior and design of extended end-plate moment connections under cyclic loading was conducted at Virginia Polytechnic Institute and State University. Six bare steel beam-to-column connection specimens and one composite slab beam-to-column connection specimen were tested. An overview of the design, fabrication, and testing of the specimens is presented. The test results show that extended end-plate moment connections can be designed to provide the strength, stiffness, and ductility required for use in seismic force resisting moment frames. The effects of the composite slab are discussed, and it is recommended that the effects of the slab be considered in the design of beam-to-column extended end-plate moment connections.